Comparative morphology of spheroidized pearlite steel by optical and electron - microscopic methods - V. V. Gerasimov (Известия высших учебных заведений: Проблемы энергетики)
Pearlite steel 12H1MF from the main steam line control meter run of Kazan CHP-3 after designed production life of 100,000 hours operation was investigated. The study was performed using an optical microscope Neofet - 32 and multi-scanning electron microscope EVO - 50 comparative analysis of the steel surface morphology. The possibility of electron microscopy using to evaluate the points of spheroidization is considered.